Implementasi Tahapan Pengembangan Masyarakat Dalam Program Perhutanan Sosial - Faizal, Ahmad Nur; Sunan, Moch. Ilham Noer (Jurnal Ilmu Kesejahteraan Sosial, 2023)
The community's dependence on the forest makes the community's position vulnerable when access to the forest is restricted. The restrictions on community access to forests impact on emerging social problems such as poverty, conflict, and illegal logging. Responding to this problem, the government rolled out a social forestry program to improve people's lives. This research uses a qualitative approach with data collection techniques through observation, semi-structured interviews, and documentation to study in depth how the community development stages are implemented in the social forestry program in Burno Village. The results showed that there were community development efforts from CDK Lumajang to LMDH Wono Lestari and Pesanggem, especially in capacity building activities. This is intended so that Pesanggem who gets management rights to the forest can utilize the potential of forest resources in a planned and organized manner to create an increase in community welfare. The realization of the social forestry Burno Village doesn't only focus on managing the forest area (on-farm), but is also directed to developing business potential outside the forest area (off-farm).